Cryptorchidism and Fertility - Fatma Fawzy; Amr Hussein; Mostafa Mahmoud Eid; Ahmed Mahmoud El Kashash; Hosni Khairy Salem (SAGE Publishing, 2015)
Cryptorchidism, the failure of one or both testes to descend into the scrotum prenatally, occurs in 2.4%-5% of newborns. Many of these testes will descend spontaneously shortly after birth, but ~23% will remain undescended unless surgery is performed. Bilaterally cryptorchid men have a six times greater risk of being infertile when compared with unilaterally cryptorchid men and the general male population. Approximately 10% of infertile men have a history of cryptorchidism and orchidopexy. The main reasons for infertility in men with a history of cryptorchidism treated by orchidopexy are maldevelopment of the testes and an improper environment for the normal development of the testes, hyperthermia, and antisperm antibodies.